PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN RETURN ON EQUITY (ROE) TERHADAP DIVIDEND PAYOUT RATIO (DPR) PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA (BEI) TAHUN 2013 –2017 - Purba, Dianty Putri; Sheren, .; Valent, .; Angeline, . (Universitas Sam Ratulangi, 2019)
The objective of this study is to analyze the effect of current ratio (CR), debt to equity ratio (DER), and return on equity (ROE) to dividend payout ratio (DPR) on consumer goods industry listed in Indonesia Stock Exchange along period of 2013-2017. This study uses quantify method with explanatory approach. The sample of this study is 41 firms and conducts multiple regressions for hypothesis testing. This study shows that current ratio, debt to equity ratio, and return on equity simultaneously effect on dividend payout ratio for consumer goods industry listed in Indonesia Stock Exchange along period of 2013-2017 with result F=15,303. Partially, current ratio and debt to equity ratio are insignificant to dividend payout ratio while return on equity has significant and positive with result t =5,398. The determinant coefficient of 0,352 shows that CR, DER, and ROE can explain DPR for 35,2% while the rests or about 64,8% can be explained by other factors excluded for this study.